The comparison between folic acid supplementation compared to calcium supplementation as preeclampsia prevention: a systematic review - Angelius, Chelsie; Torizal, Fuad Gandhi (International Journal of Health Science and Technology, 2024)
Preeclampsia is a major cause of adverse pregnancy outcomes for both mothers and infants, leading to higher rates of morbidity and mortality. Despite progress in prenatal care, the exact cause of Preeclampsia remains unknown, highlighting the need for effective prevention strategies to improve outcomes. Various nutritional interventions can be used as potential preventive measures against Preeclampsia. Among these, folic acid and calcium supplementation have garnered considerable attention. This systematic review aims to compare the effectiveness of folic acid versus calcium supplementation in preventing Preeclampsia. By synthesizing the current evidence, we seek to elucidate the relative benefits of these two interventions, thereby providing clearer guidance for clinical practice and future research.  This systematic review uses PubMed Central, Springerlink, PubMed, and Google Scholar as databases, using MeSH (Medical Subject Headings) terms: ‘Folic Acid’, ‘Calcium’, and ‘Preeclampsia’ to extract relevant publications. Publications included were limited to English publications in the past 5 years globally. This study included 6 studies compromising 29.664 women. Prisma table is used to identify studies via databased and sorted with Rayyan.ai. Both Calcium and Folic acid supplementation in adequate dose equally needed to prevent preeclampsia. Further research is necessary to evaluate the effectiveness of therapy in equivalent subject groups. There is currently limited information on the impact of health supplements on high-risk pregnancies, including the effects of calcium supplementation.